Limiting high pressure rate coefficients for the HO+NO2&→HONO2 reaction on ab initio potential energy surfaces - Cobos, Carlos Jorge (2003)
Phase space limiting high pressure rate coefficients for the title reaction on ab initio potential energy surfaces have been calculated at 50-600 K. Calculated rigidity factors at different levels of theory are presented. The best limiting high pressure rate coefficient obtained at 300 K, 4.0x10-11cm3 molecule-1 s-1, compares very well with the latest IUPAC recommended value.